1998
DOI: 10.1002/masy.19981260108
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of ionic amphiphils by oppositely charged polyelectrolyte gels

Abstract: Slightly cross‐linked polyelectrolytes absorb oppositely charged surfactants in aqueous media. Transfer of amphiphilic ions from solution into the swollen network proceeds as a frontal heterogeneous cooperative reaction causing a collapse of the original polyelectrolyte gel. Small and wide angle X‐ray diffraction data show that electrostatic complex formed as a result of the reaction consists of lamellar type surfactant micelles embedded in a polyelectrolyte network. It is also shown that such complexes contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 7 publications
2
33
0
Order By: Relevance
“…In the year 1990, Starodubtzev et al published the first report of surfactant-rich shells in polyelectrolyte gels [17]. Shortly after, the group of Zezin and Kabanov (Z&K) reported that binding of short polyion chains and proteins could give rise to similar phenomena [18,[81][82][83][84][85][86]. The early observations of surfactant-rich shells were made on gels of macroscopic size (~1 mL), that either had been immersed for a short time in a "salt-free" surfactant solution and then transferred to pure water, or stored long times in solutions containing limited amounts of the surfactant.…”
Section: Shell Composition and Microstructurementioning
confidence: 99%
“…In the year 1990, Starodubtzev et al published the first report of surfactant-rich shells in polyelectrolyte gels [17]. Shortly after, the group of Zezin and Kabanov (Z&K) reported that binding of short polyion chains and proteins could give rise to similar phenomena [18,[81][82][83][84][85][86]. The early observations of surfactant-rich shells were made on gels of macroscopic size (~1 mL), that either had been immersed for a short time in a "salt-free" surfactant solution and then transferred to pure water, or stored long times in solutions containing limited amounts of the surfactant.…”
Section: Shell Composition and Microstructurementioning
confidence: 99%
“…When the gel is placed in a solution containing oppositely charged surfactant of a concentration exceeding the critical association concentration (cac), but of equal ionic strength, the surfactant monomers will diffuse into the gel and there form micelles [11]. This allows the release of the counter ions previously neutralizing the polymer charges and, due to the subsequent lowering of the swelling pressure, causes the gel to collapse [1,4,6]. As micelles form in the gel, the outer part will collapse first, causing a phase separation with a dense, outer, micelle rich surface phase and a still swollen, micelle lean core [1][2][3]5].…”
Section: Introductionmentioning
confidence: 99%
“…For some of these a non-uniform deswelling with the formation of a surface phase has been reported [1][2][3]5,6,8,9]. In general, a polyelectrolyte gel, such as a crosslinked polyacrylate (PA) or hyaluronate (HA) gel, is in its reference state swollen due to the swelling pressure provided by the counter ions present inside the gel [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations